Ebola virus outbreaks in Africa: Past and present - Muyembe-Tamfum, J.J.; Mulangu, S.; Masumu, Justin; Kayembe, J.M.; Kemp, A.; Paweska, Janusz T. (Onderstepoort journal of veterinary research, 2012)
Ebola haemorrhagic fever (EHF) is a zoonosis affecting both human and non-human primates (NHP). Outbreaks in Africa occur mainly in the Congo and Nile basins. The first outbreaks of EHF occurred nearly simultaneously in 1976 in the Democratic Republic of the Congo (DRC, former Zaire) and Sudan with very high case fatality rates of 88% and 53%, respectively. The two outbreaks were caused by two distinct species of Ebola virus named Zaire ebolavirus (ZEBOV) and Sudan ebolavirus (SEBOV). The source of transmission remains unknown. After a long period of silence (1980–1993), EHF outbreaks in Africa caused by the two species erupted with increased frequency and new species were discovered, namely Côte d’Ivoire ebolavirus (CIEBOV) in 1994 in the Ivory Coast and Bundibugyo ebolavirus (BEBOV) in 2007 in Uganda. The re-emergence of EHF outbreaks in Gabon and Republic of the Congo were concomitant with an increase in mortality amongst gorillas and chimpanzees infected with ZEBOV. The human outbreaks were related to multiple, unrelated index cases who had contact with dead gorillas or chimpanzees. However, in areas where NHP were rare or absent, as in Kikwit (DRC) in 1995, Mweka (DRC) in 2007, Gulu (Uganda) in 2000 and Yambio (Sudan) in 2004, the hunting and eating of fruit bats may have resulted in the primary transmission of Ebola virus to humans. Human-to-human transmission is associated with direct contact with body fluids or tissues from an infected subject or contaminated objects. Despite several, often heroic field studies, the epidemiology and ecology of Ebola virus, including identification of its natural reservoir hosts, remains a formidable challenge for public health and scientific communities.